Dredging technology at placer gold deposits in the Far North - Ravil Z Nafikov; Victor E Kislyakov; Aleksandr K Kirsanov; Umarjon R Teshaev (Brawijaya University, 2023)
The volumes of world gold mining were reviewed. As a result of the analysis, it was found that the proportion of placer gold is very insignificant. This is due to the fact that the most easily accessible reserves are substantially depleted, and the development of deposits with complex mining and geological conditions, including those located in the Far North, is economically impractical. To solve this problem, a method was proposed for isolating the dredging open-pit from the effects of negative temperatures by a hangar-type structure. Similar structures used in the mining industry were considered. Calculations of the dimensions of the structure that allow for safe manoeuvring of the dredge were presented. The data on the duration of the dredging season when implementing the proposed solution in the conditions of the Far North were provided. A method of protecting rocks from freezing when using this technology was proposed. The technical and economic indicators confirming the effectiveness of the implementation of the proposed solution were presented.